GENDER CHARAKTERISTICS OF THE MANIFESTATION OF LEADERSHIP AMONG STUDENT YOUTH - Khomenko-Semenova, Larysa; Istratov, Kostiantyn; Oksamytna, Lesia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article carries out a theoretical analysis and an empirical study of the gender characteristics of the manifestation of leadership among student youth. The purpose of the article is the theoretical justification and empirical determination of the gender characteristics of the manifestation of leadership among student youth. The results. In the course of empirical research, it was possible to establish: clearly expressed leadership qualities are found mainly in women than in men, women show themselves to be confident, dominant, persistent. However, the comparative analysis did not reveal statistically significant differences in the manifestation of leadership qualities by gender - in men and women (according to the methodology of E. Zharikov, E. Krushelnytskyi); this quality is expressed more in men than in women. This characterizes men as persistent, they know how to manage their emotions, allocate time effectively (significant differences at the 1% level of significance); women are characterized by a more pronounced creative approach to solving difficult situations and professional tasks, like to search and try new things, easily get excited about a new business when making decisions, tend to go through several options (significant differences at the 5% level of significance); women, more than men, have pronounced "organizational abilities". This is manifested in the fact that women strive for harmonious team work, try to reach understanding and find a common language in relations with people, feel and guess the moods of their colleagues well (significant differences at the 1% level of significance); the higher the manifestations of masculinity in men, the more their leadership qualities are revealed, at the same time, the less feminine qualities are revealed in women, the more leadership qualities are revealed in them; the higher the masculinity index in men and women, the better they are able to manage themselves, maintain composure in difficult situations; The higher the femininity indicators in men, the more they are inclined to a creative approach in solving tasks; a high level of androgyny, i.e. the manifestation of both masculine and feminine traits, contributes to the development of such leadership qualities in women as "the ability to work with a group", i.e. contributes to the fact that androgynous women build effective interpersonal relationships in a group, based on trust, mutual support and understanding, at the same time, effectively solving the tasks assigned to the group. Conclusion. The higher the masculinity index in men and women, the better they are able to manage themselves, to maintain composure in difficult situations; The higher the femininity indicators in men, the more they are inclined to a creative approach in solving tasks. Feminine men’s inherent emotionality, empathy allows them to look for and try something new, choosing, among other things, creative professions. A high level of androgyny, that is, the manifestation of both male and female traits, contributes to the development of such leadership qualities in women as "the ability to work with a group", that is, it contributes to the fact that androgynous women build effective interpersonal relationships in a group, based on trust, mutual support and understanding of the assigned tasks